Strategi Pengembangan Wisata Edukasi Gurami dalam Meningkatkan Ekonomi Melalui Metode ABCD - Nur Illahi, Shita Devita (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
Gurami Seiduri Tourism is a local tourism that was originally formed by the Tourism Awareness Group community. This group consists of approximately 6 people who want to initiate community empowerment through educational tourism located in Seiduri Wonodadi Blitar. This research uses the Asset-Baseid Community Development (ABCD) method, which is one of the initiatives in empowering and improving the quality of Human Resources. The results of this service have increased awareness among the Gurami Seiduri Tourism Pokdarwis, through socialization carried out in implementing the Village Law number 6 of 2014. Pokdarwis holds the economic and economic guidelines for smart villages which are one of the pillars of smart villages. The educational tourism of Gurami Seiduri should improve the mental health of its members. The success of the balancing strategy in Gurami Seiduri Tourism in a broad sense will be able to reflect the values of community empowerment. Internal analysis in its management includes: performance analysis in the form of culinary services with various gourami fish dishes and education on gourami cultivation. The eiksteirnal analysis includes the management of all members, both internal and eiksteirnal, taking into account the network with relevant policy stakeholders, partnerships in local tourism management in Blitar, for example the Local Guidei, tourism awareness groups and other communities. Keywords: Balancing, Educational Tourism, Economic Improvement